CURRICULUM MANAGEMENT STRATEGIES AND EFFECTIVE IMPLEMENTATION OF UNIVERSAL BASIC EDUCATION IN NIGERIA - Nimota Jibola Kadir Abdullahi (Universitas Tanjungpura, 2022)
The main goal of this research was to investigate how curriculum management strategies affected the successful implementation of Universal Basic Education. Total of 712 participants were chosen using proportional random sampling from the sampled primary and junior secondary schools in North-west, Nigeria. The findings of the study demonstrated that students’ mastery goal, effective classroom instruction and evaluation all helped to improve the effectiveness of UBE implementation. Pearson product moment correlation coefficient and linear regression analysis were used to test the hypotheses. Thus, it was recommended that school managers should encourage students' mastery goal so as to help learners to better engaged in the learning process. Likewise, school managers should strive to create effective classroom instruction to help in engaging learner with concepts and process for learning. Furthermore, evaluation of curriculum and learners activities should be done frequently in order to determine learners’ competence before, during and after instruction toward effective implementation of curriculum. Keywords: students' mastery goal; effective classroom instruction, evaluation; self-efficacy; curriculum.